Magnesium Based Hybrid Nanocomposites: An Insight into Nanoparticle Effects on the Microstructure and Mechanical Properties - Seetharaman, Sankaranarayanan; Subramanian, Jayalakshmi; Singh, Ramachandra A.; Gupta, Manoj (Current Nanomaterials, 2021)
Aims: The primary aim of this research is to understand the effects of type of nanoparticles on the microstructure and mechanical properties of Mg-based hybrid nanocomposites. For this reason, new Mg-based hybrid nanocomposites containing 2.2 vol.% Ti and 1.1 vol.% nano-Al2O3 or nano B4C particles were synthesized and their properties were studied in comparison with Mg- Ti and pure Mg. Background: Magnesium with excellent weight-saving potential is ideal for automotive and aerospace applications. But its use in pure Mg is restricted due to inherent limitations such as poor absolute strength, elastic modulus, deformability, and corrosion susceptibility. While most of these limitations can be circumvented by the judicious addition of micron-sized ceramic reinforcements, ductility is often compromised. One of the promising ways for ductility enhancement involves the use of nano-length scale reinforcements. Similar ductility improvements were also reported when hybrid reinforcements were introduced into the Mg matrix. While the role of hybrid reinforcement preparation, the particle size distribution, and volume fraction of hybrid reinforcements were studied extensively in the past, no detailed investigation on the effects of type of nanoparticles has been conducted so far. Objective: The objectives of this research include the successful synthesis and property characterization of Mg-based hybrid nanocomposites containing hybrid (Ti+Al2O3 or Ti+B4C) reinforcements. Methods: Effects of the type of nanoparticles on the properties of Mg-based hybrid nanocomposites were studied by invoking the process-microstructure-property relationships. Results: While both hybrid nanocomposites displayed fine grains when compared to pure Mg and Mg-Ti, there was no noticeable difference between the grain size distribution profiles of Mg- (Ti+Al2O3) and Mg-(Ti+B4C) hybrid composites. The results of property measurements indicated an improvement in dimensional stability, indentation, tension, and compression properties of Mg due to the addition of either individual Ti or hybrid (Ti+Al2O3) or Mg-(Ti+B4C) particles. Among the hybrid composites, Mg-(Ti+B4C) containing hybrid (Ti+B4C) reinforcement exhibited a better combination of strengths and ductility. While the inherent strengthening contribution from B4C and Al2O3 reinforcements resulted in slightly different strength properties, the ductilization benefits of boron compounds enhanced the tensile fracture strain of Mg-(Ti+B4C). Conclusion: Since the particle size distribution and volume fraction of (Ti+Al2O3) and (Ti+B4C) are similar, the difference in strength values between Mg-(Ti+Al2O3) and Mg-(Ti+B4C) can be attributed to the matrix strengthening contribution from reinforcement type.
Keywords: metal matrix composites